The potential role of everolimus after kidney transplantation - Tedesco-Silva Jr, Helio; Prismich, Glaucia (Brazilian Journal of Transplantation, 2006)
The long-term graft survival rates are still relatively low. The use of some novel immunosuppressant, which played a significant role in reducing the risk of acute rejection, does not prevent the development and progression of chronic allograft dysfunction. The aim of this article is to provide a review on the use of everolimus as immunosuppressive therapy for kidney transplant recipients, and on its potential role in preventing chronic allograft nephropathy. Articles published on Pubmed and Lilacs between 1997 and 2007, were considered for this review and were eligible those comparing the use of everolimus versus mycophenolate mofetil or azathioprine in transplant recipients and also articles that focused renal transplant complications. Chronic allograft nephropathy, whose biopsy proven prevalence may be as high as 94% in the first post-transplantation year has some risk factors such as: episodes of acute rejection; cytomegalovirus infection; nephrotoxicity induced by calcineurin inhibitors and comorbidities, such as diabetes mellitus, hypertension and dyslipidemia. Everolimus, a potent immunosuppressant that works as an inhibitor of cellular proliferation has a potential efficacy in preventing chronic allograft dysfunction, when combined with cyclosporine.